ANALISIS KEBUTUHAN TENAGA PERAWAT DENGAN METODE WORKLOAD INDICATOR STAFFING NEED (WISN) DI RUANG INTERNA INSTALASI RAWAT INAP RSD Dr. SOEBANDI JEMBER - Abu Khoiri; Dyah Kusworini; Ari Purwanto (Jurnal Ilmu Kesehatan Masyarakat, 2011)
Nursing services in the hospital for 24 hours a day, that have constant contact with the patient. Therefore, the nursing services at the hospital is an integral part of health care and contribute highly to determine the quality of hospital services. Based on patient data visit of Inpatient Installation of RSD Dr. Soebandi Jember which have increased from year to year, especially the highest number at interna unit. So that the necessary studies to calculate the optimal needs of nurses in the internal ward inpatient installation by the WISN (Workload Indicator Staffing Need) method . This study aims to determine the optimal number of nursing staff requirements in Section Inpatient Unit Interna of RSD. Dr. Soebandi based on real workload with WISN method. This study is a descriptive study with quantitative data analysis by the method of work sampling. The data was collecting used work sampling form. Samples were chosen activities every ten minutes which done by staff in 24 hours. Primary data collected by observation of worker activity pattern in six days. Secondary data source collected from medical record and human resources unit in Dr. Soebandi Hospital Jember. The results showed that the use of productive time of the total available working time is 76.5%. With details of the productive activity of 26.16% direct, indirect productive by 37.19% and 13.12% of nonfunctional. Based on WISN calculation method, the number of personel that needed is 25 people. So with the result that concludes, this time Interna Ward requires one more personel. Key Words : WISN, work load, nurse